BARRIERS TO THE INVOLVEMENT OF TOURISM ACTORS IN THE IMPLEMENTATION OF SUSTAINABLE TOURISM: A STUDY ON TOURISM ACCOMMODATION SECTOR OF BALI - Iswara A.M.Y.; Astawa I N.D.; Suyasa D.; Diana W. (Russian Journal of Agricultural and Socio-Economic Sciences, 2023)
Sustainable tourism is the dream of every destination by harmonizing economic, social and environmental aspects in every strategic tourism activity, especially after the COVID-19 pandemic hit almost two years ago. The concept of sustainability is not as easy as it is echoed both in theory and practice in the field. Sustainability is seen as difficult to measure and operationalize due to authority barriers and the term sustainability, which is used in various contexts and situations, means different things to different people. The purpose of this study is to identify and evaluate barriers to the implementation of sustainable tourism in the tourism accommodation sector in Bali. This research is a qualitative approach. Data collection methods in this research are literature, observation, interview, and Focus Group Discussion. This research is supported by experts, namely the government, the tourism industry, especially hotel general managers, academics and the community using purposive sampling techniques. The result of this research is that 4 main reasons hinder the implementation of sustainable tourism in the accommodation sector in Bali, namely 1) Companies only focus on profit or profit, 2) There is a conflict of interest that occurs between investors and tourism accommodation managers, 3) Running the concept of sustainability just to get legitimacy, and 4) Competition in room rental prices has implications for the cheapening of tour package offers. Suggestions that can be proposed are the awareness and commitment of tourism accommodation actors to be critical so that companies do not make a profit as the ultimate goal in business, but actively participate in efforts to realize sustainable tourism development in Bali.